2019
DOI: 10.1302/0301-620x.101b6.bjj-2018-0723.r3
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative management of Hepatitis C may improve the outcome after total knee arthroplasty

Abstract: Aims With an ageing population of patients who are infected with hepatitis C virus (HCV), the demand for total knee arthroplasty (TKA) in this high-risk group continues to grow. It has previously been shown that HCV infection predisposes to poor outcomes following TKA. However, there is little information about the outcome of TKA in patients with HCV who have been treated successfully. The purpose of this study was to compare the outcomes of TKA in untreated HCV patients and those with HCV who have been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…We noted that nearly 45% of our patient cohort (125 TJA cases) did not receive treatment and had PVL when undergoing TJA, and many of them refused treatment due to the limitations and side effects of interferon. That being said, patients undergoing TJA treated with DAAs do not have lower medical or surgical complications, PJI, and revision TJA rates for mechanical causes than those treated with interferon [ 25 ]. In our study, patients receiving interferon or DAAs achieved high UVL rates, and the type of treatment was not a significant risk factor for developing PJI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that nearly 45% of our patient cohort (125 TJA cases) did not receive treatment and had PVL when undergoing TJA, and many of them refused treatment due to the limitations and side effects of interferon. That being said, patients undergoing TJA treated with DAAs do not have lower medical or surgical complications, PJI, and revision TJA rates for mechanical causes than those treated with interferon [ 25 ]. In our study, patients receiving interferon or DAAs achieved high UVL rates, and the type of treatment was not a significant risk factor for developing PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Schwarzkopf et al. found that liver fibrosis is more prevalent in patients who received treatment for HCV than in those not treated, indicating that treatment was preferentially given to those patients with advanced disease [ 25 ]. We identified a similar trend in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…As these patients often have more comorbidities than most patients undergoing an rTKA and higher comorbidity burdens are associated with an increased complication risk [ [41] , [42] , [43] , [44] ], medical optimization before an rTKA is critical in this population. Recent analyses have reported improved outcomes after a primary arthroplasty in patients with HCV who received preoperative antiviral treatment [ 16 , [45] , [46] , [47] ]. It is likely that similar interventions before an rTKA also decrease the complication risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…It was not until 2019 that Medicaid in Louisiana expanded to include hepatitis C treatment for all patients [39]. Recent studies demonstrate the possible benefits associated with treatment of hepatitis C [11,40,41]. Future studies should examine the effects of treated vs untreated hepatitis C patients using a very large patient population examining complications using clinical and ICD coding data.…”
Section: Discussionmentioning
confidence: 99%